2008
DOI: 10.1073/pnas.0805364105
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes with lid-gated active sites must operate by an induced fit mechanism instead of conformational selection

Abstract: The induced fit and conformational selection/population shift models are two extreme cases of a continuum aimed at understanding the mechanism by which the final key-lock or active enzyme conformation is achieved upon formation of the correctly ligated enzyme. Structures of complexes representing the Michaelis and enolate intermediate complexes of the reaction catalyzed by phosphoenolpyruvate carboxykinase provide direct structural evidence for the encounter complex that is intrinsic to the induced fit model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
217
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(231 citation statements)
references
References 50 publications
11
217
3
Order By: Relevance
“…Two common features of most protein-ligand systems are that the energy surface switches from favoring nonreactive conformations while the ligand is away to favoring reactive conformations while the ligand is near and the reactive region is highly localized. 25,26 We have also presented a method for calculating the binding rate constant from Brownian dynamics simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Two common features of most protein-ligand systems are that the energy surface switches from favoring nonreactive conformations while the ligand is away to favoring reactive conformations while the ligand is near and the reactive region is highly localized. 25,26 We have also presented a method for calculating the binding rate constant from Brownian dynamics simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite such successes, there are many examples of systems that cannot be explained by conformational selection. For example, Sullivan and Holyoak (35) showed that in phosphoenolpyruvate carboxykinase (PEPCK) formation of the catalytic active complex is combined with a closure of the active site. This means that, even if in the unbound state PEPCK samples bound conformations, they would simply not be available for the substrate.…”
mentioning
confidence: 99%
“…The enediol intermediate is susceptible to loss of phosphate by ␤-elimination (46). To avoid this side reaction, triosephosphate isomerase uses a mobile loop as a lid to sequester the active site following ligand binding (47) Similar lid gating mechanisms are common, making those with uncommon properties particularly interesting (48) Luciferase is unusual because of its distinct reaction chemistry and an unusually long mobile loop consisting of ϳ30 residues. The first aim of this study was to determine whether any labile intermediates might be protected by the bacterial luciferase mobile loop.…”
Section: Discussionmentioning
confidence: 99%